Analisis Sentimen Film Squid Game Melalui Platform X Menggunakan Metode Lexicon Based - Anggoro, Deo; Alessandro, Andreas; Aditya, Putra; Wijaya, Andri (MDP Student Conference, 2025)
This study discusses the role of movies as a medium in conveying social and emotional messages, with a focus on the Squid Game series. This research applies Lexicon-Based sentiment analysis to evaluate audience reactions to the series using 10,000 tweets from Twitter (X). The results of the analysis showed that 36.3% of the comments had a positive sentiment, 46.4% were neutral, and 17.2% were negative. The majority of neutral sentiment indicates that many viewers were interested but did not have strong opinions, while the significant positive sentiment indicates a favorable reception to the movie. These results provide insight into how audiences responded to the themes of economic inequality and social oppression in the movie. This analysis highlights the relevance of sentiment analysis in understanding audience responses to social issues, as well as how films can reflect deeper cultural and social issues.